Taking a closer look: an SEM review of Levinsenia species (Polychaeta: Paraonidae) reported from California - Lovell, Lawrence L.; Fitzhugh, Kirk (Zootaxa, 2020)
Scanning electron (SEM) and light microscope examinations of members of Levinsenia Mesnil, 1897, species from California yielded a new species, new characters, emended name and range extension for L. kirbyorum Lovell, 2002. Specimens of L. gracilis (Tauber, 1879) from Sweden, Iceland, and California were compared and could not be distinguished on the basis of morphology. Two other Californian species, L. multibranchiata (Hartman, 1957) and L. oculata (Hartman, 1957), were also examined. SEM revealed features previously undescribed for the genus. Additional prostomial ciliary bundles, dorsal transverse ciliary branchial connections, notopodial sensory pores, and neurochaetal fascicle configurations. Levinsenia barwicki n.sp. possessing a terminal sensory organ, 4-8 leaf-like ciliate branchiae, and recurved neurochaete with distal hood is described More SEM work is necessary to confirm if these features are present among other members of Levinsenia and other Paraonidae genera. The status of Levinsenia according to the phylogenetic analysis performed by Langeneck et al. (2019, Molecular Phylogenetics and Evolution, 136, 1-13) is discussed.